2020
DOI: 10.1016/j.ajo.2020.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Axial Length Adjustment Methods on Intraocular Lens Power Calculation in Highly Myopic Eyes

Abstract: Super formula (LSF), and Emmetropia Verifying Optical formulas in highly myopic eyes.DESIGN: Retrospective, consecutive case-series study. METHODS: A total of 164 eyes of 164 patients with AL ‡26.0 mm were included and divided into 2 groups: AL <28.0 mm (Group 1) and AL ‡28.0 mm (Group 2). The average arithmetic spherical equivalent prediction error (PE), mean absolute PE, median absolute error (MedAE), and the percentage of eyes within ±0.25 diopter (D), ±0.50 D, and ±1.0 D of PE were determined. RESULTS: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Previous studies have reported that the Kane formula and traditional formulas with WK AL adjustment exhibited higher prediction accuracy in highly myopic eyes. [23][24][25][26][27][28][29] In this study, we also observed that Kane and traditional formulas with WK AL adjustment displayed better prediction accuracy in PIOL implanted eyes. This could be partly due to that the study participants were all highly myopic with an average AL of 31.43 ± 2.15 mm.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have reported that the Kane formula and traditional formulas with WK AL adjustment exhibited higher prediction accuracy in highly myopic eyes. [23][24][25][26][27][28][29] In this study, we also observed that Kane and traditional formulas with WK AL adjustment displayed better prediction accuracy in PIOL implanted eyes. This could be partly due to that the study participants were all highly myopic with an average AL of 31.43 ± 2.15 mm.…”
Section: Discussionmentioning
confidence: 55%
“…The accuracy of the formula was evaluated by the following steps. 25 First, each prediction error (PE) was calculated as the difference between the postoperative and formula-predicted spherical equivalent (SE) using the IOL power implanted. The BUII, EVO, Haigis, Hoffer Q, Holladay 1, Kane, LSF, and SRK/T formulas were calculated for all patients, while the Haigis, Hoffer Q, Holladay 1, and SRK/T with the first linear (WK1), second linear (WK2), and nonlinear (WKn) versions of WK AL adjustment were evaluated in patients with AL >26 mm.…”
Section: This Was a Retrospective Consecutive Case Seriesmentioning
confidence: 99%
“…In 2020, several studies with measurements taken by IOLMaster700 were published. In a study of 164 eyes of AL longer than 26.00mm by Zhang et al, [19] EVO was found to have a MAE of 0.35D and 79.27% of patients achieving a refractive error within ±0.50D, better than Barrett Universal II (0.38D, 73.17%).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the EVO formula achieved the second-lowest MAE of 0.335D, a MedAE of 0.285D, 78.4% and 96.9% of eyes within ±0.50D and ±1.00D respectively, which was comparable to the results of previous studies. [16,19] In eyes of AL within 26.00mm and 28.00mm, EVO was ranked rst with an MAE of 0.328D, while in eyes of AL longer than 28.00mm, EVO had a higher MAE than Kane and Hill-RBF3.0 formulas. This is consistent with the viewpoint of Melles et al [15] that the emmetropization concept may break down at the extremes of the axial lengths.…”
Section: Discussionmentioning
confidence: 95%